Determinismo causal e reponsabilidade moral : o semicompatibilismo de John Martin Fischer - João Paulo Oliveira Alves (2021)
The object of analysis of this research is the compatibility between causal determinism and moral responsibility as proposed by John Martin Fischer. To do this, first, we will assess some of the main challenges that causal determinism poses to our moral agency. Among these challenges, the Principle of Alternate Possibilities will be considered and examined by drawing on Harry G. Frankfurt cases. Next, we will present Fischer’s semicompatibilism with a focus on the two main components of guidance control, the type of control needed for moral responsibility: reasons-responsiveness and mechanism ownership. Lastly, we will analyze (i) the views of the incompatibilist philosopher Derk Pereboom on Frankfurt cases and on Fischer’s semicompatibilism, and (ii) Fischer’s criticism of inflated notions of control and origin.